2011
DOI: 10.1128/jcm.02601-10
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-Resistant Staphylococcus aureus Colonization at Different Body Sites: a Prospective, Quantitative Analysis

Abstract: We quantified methicillin-resistant Staphylococcus aureus (MRSA) carriage. The greater the log 10 count in samples from the nares, the greater the likelihood that other body sites had been colonized. Log 10 counts among body sites were correlated. The greatest sensitivity value (98%) was determined for the combined results from 2 sites: the nares and the groin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 22 publications
2
47
0
6
Order By: Relevance
“…A high concentration of MRSA on chromogenic media most certainly represents a true transmission concern and needs to be immediately reported to infection control. Several factors may contribute to the recovery of MRSA, such as interfering substances (e.g., nasal sprays), patient age and immunosuppression, body site, and proper specimen collection, However, Mermel et al (11) showed that the quantity of MRSA in the nares correlated inversely with the likelihood of MRSA infection.…”
Section: Discussionmentioning
confidence: 99%
“…A high concentration of MRSA on chromogenic media most certainly represents a true transmission concern and needs to be immediately reported to infection control. Several factors may contribute to the recovery of MRSA, such as interfering substances (e.g., nasal sprays), patient age and immunosuppression, body site, and proper specimen collection, However, Mermel et al (11) showed that the quantity of MRSA in the nares correlated inversely with the likelihood of MRSA infection.…”
Section: Discussionmentioning
confidence: 99%
“…3 A 2010 survey 4 of 590 US health care facilities indicated that the overall prevalence of MRSA in these institutions was 66.4 per 1000 inpatients. The prevalence of colonization was 41.1 per 1000 inpatients, and the infection rate was 25.3 per 1000 inpatients.…”
Section: Outcomes and Data Collectedmentioning
confidence: 99%
“…Serial dilutions of the broth were spiral plated onto Spectra MRSA agar; colonies were counted at 24 h and converted to log 10 CFU/ml (12). Using this method, 73/76 PCR-positive partner swabs grew MRSA.…”
mentioning
confidence: 99%
“…An additional advantage of PCR-based tests is an easily obtained measure of quantification in the C T . Quantification of nasal S. aureus colonization was described over 50 years ago and has been linked to the persistently colonized state (14,20), an increased risk of contamination of the environment (5,17), an increased risk of infection (10,19), and a higher likelihood that other body sites (besides the nares) are colonized (12). In those studies, S. aureus carriage was quantified by labor-and time-intensive techniques not easily implemented in a clinical practice.…”
mentioning
confidence: 99%